A control based protection adaptability improving strategy for transmission line with renewable energy integration. (July 2023) - Ji, Liang; Tong, Yiqi; Yu, Zilin; Jiang, Enyu; Xi, Ruiling; Yin, Jiaming; Fu, Yang
Highlights: Adaptability analysis of differential protection and distance protection on transmission line with renewable energy. An active control scheme is proposed to eliminate the adverse effects of RES in power grid. Restrain the influence of transition resistance and effectively resolve the problems of refusing action or malfunction of distance protection. Improve protection performance without changing the existing protection devices. Abstract: The protection performance of transmission line with renewable energy (RE) infeed are greatly challenged by the uncertain characteristics of RE, which not only influences the magnitude of infeed fault current and voltage from RE, but also changes the phases of such parameters, compared with conventional power source. As a result, both differential protection and distance protection may work improperly. This paper proposed a control-based protection improving strategy by applying the highly controllable characteristics of inverter-interfaced renewable energy (IIRG) to solve such impacts. Firstly, the adaptabilities of differential protection and distance protection on transmission line with renewable energy infeed are analyzed. Then, a new IIRG control strategy is introduced which is capable to control the voltage and current phase following the forementioned protection adaptability analysis. Then, the configuration and settings of protections are updated. Finally, the effectiveness of the proposed method is verified by Matlab/Simulink simulation. The proposed method provides a theoretical basis for the IIRG control as to improve the protection performance without changing the existing protection devices.